Large-Scale Ontology Development and Agricultural Application Based on Knowledge Domain Framework - Xian-xue MENG; Jing LI; Xiao-lu SU; Hai-yan HU; Yi-qian WANG (Journal of Integrative Agriculture, 2012)
The key activity to build semantic web is to build ontologies. But today, the theory and methodology of ontology construction is still far from ready. This paper proposed a theoretical framework for massive knowledge management – the knowledge domain framework (KDF), and introduces an integrated development environment (IDE) named large-scale ontology development environment (LODE), which implements the proposed theoretical framework. We also compared LODE with other popular ontology development environments in this paper. The practice of using LODE on management and development of agriculture ontologies shows that knowledge domain framework can handle the development activities of large scale ontologies. Application studies based on the principle of knowledge domain framework and LODE was described briefly.